2002
DOI: 10.1080/10588330208951209
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Polyaromatic Hydrocarbon-Contaminated Sediments in Aerated Bioslurry Reactors

Abstract: Treatment of dredged sediments contaminated by polyaromatic hydrocarbons (PAHs) is a significant problem in the New York/New Jersey (NY/NJ) Harbor. 0.5 m--scale slurry-phase bioreactors were used to determine whether bioaugmentation with a PAH-degradative bacterial consortium, or with the salt marsh grass S. alterniflora, could enhance the biodegradation of PAHs added to dredged estuarine sediments from the NY/NJ Harbor. The results were compared to biodegradation effected by the indigenous sediment microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
3
14
0
1
Order By: Relevance
“…Variation in salinity is a predominant factor in mangroves and depends on the behaviour of the tides (Ward and Brock 1978;Dott et al 1989, Shiaris 1989Leahy and Colwell 1990;Trevors et al 1994;Kastner et al 1998;Launen et al 2002;Saponaro et al 2002;Tam et al 2002;Olguín et al 2007;Chen et al 2008;Wu et al, 2008;Mnif et al 2009) In some mangroves the most significant factors observed to affect the biodegradation of oil compounds is salinity…”
Section: Salinitymentioning
confidence: 97%
“…Variation in salinity is a predominant factor in mangroves and depends on the behaviour of the tides (Ward and Brock 1978;Dott et al 1989, Shiaris 1989Leahy and Colwell 1990;Trevors et al 1994;Kastner et al 1998;Launen et al 2002;Saponaro et al 2002;Tam et al 2002;Olguín et al 2007;Chen et al 2008;Wu et al, 2008;Mnif et al 2009) In some mangroves the most significant factors observed to affect the biodegradation of oil compounds is salinity…”
Section: Salinitymentioning
confidence: 97%
“…Only a very few studies have compared microbial petroleum hydrocarbon degradation in vegetated versus non-vegetated marine and salt marsh sediments in the lab (Wright et al 1997(Wright et al , 2004Launen et al 2002) or the field (Garcia-Blanco et al 2007) and with the exception of the studies conducted by Daane et al (2001Daane et al ( , 2002 none have characterized the specific PAH-degrading microbial communities present in Spartina-dominated petroleum impacted salt marshes.…”
Section: Introductionmentioning
confidence: 97%
“…Experiments of extensive biological degradation were performed in well-defined conditions by treating PAH-polluted soils in bench-scale stirred reactors (bioslurry reactors) [4,12]. In some case, the addition of "outer" micro-organisms has been considered a valuable tool for increasing the rate and extent of biodegradation of PAHs [3].…”
Section: Introductionmentioning
confidence: 99%